(untitled) (Research, Society and Development, 2022)
Paper-based packaging is abundant, non-toxic, from renewable resource, biodegradable material and of low marketing cost compared to other conventional materials. However, paper offers low resistance to water vapor, oils and gases, which may restrict its use for perishable products. As an alternative, biopolymers are used for coating papers, such as cellulose derivatives, starches, chitosan or chitin, proteins (animal or vegetable) and lipids. These biopolymers offer advanced and enhanced properties when used for coating papers. The objective of this review is to address the main biopolymers studied and tested for coating paper in food packaging, describing their main characteristics, in addition to presenting works that show that the mentioned biopolymers have shown to be promising, having compatible properties for the use on a large scale in the coating of paper in packaging. With this work, we hope to contribute to the advancement of scientific research and projects that promote the use of biopolymers in paper coating for use in production of food packaging.